Penggunaan Media Pohon Angka Untuk Meningkatkan Kemampuan Mengenal Konsep Bilangan Pada Anak Kelompok B TK Mutiara Kecamatan Siak Hulu Kabupaten Kampar - Amin, Muhammad; Rahayu, Evi; Guswanti, Nelia (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
This research was conducted in two cycles and each cycle was conducted in two meetings. In order to ensure this classroom action researchrun well, the researcher arranges the stages: 1) Action planning/preparation, 2) Action implementation, 3) Observation, and 4) Reflection. The subjects in this study were 14 students of B1 class consist of 8 girls and 6 boys in the first semester of the 2021/2022 academic year at TK Mutiara Kindergarten, Siak Hulu, Kampar. Meanwhile , the object of this research was the use of number tree media to improve the ability to recognize the concept of numbers of early childhood students . The research data were collected through teacher observation techniques and early childhood students' activities and documentation. After the data was collected through observation, the data was processed using the percentage form. The results of this study are there is an increasing in the learning process carried out by the teacher and the early childhood students' ability to recognize the concept of numbers. Observation of children's activities also increased, this can be seen from the pre action’s data to cycle II meeting 2. Initial data was 43.62%, Cycle II meeting 2 obtained 84.69%. So that the overall increase in early childhood students' activities to recognize the concept of numbers obtained 41.07%.